2022
DOI: 10.3389/fcimb.2021.763507
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiome and Metabolites Are Altered and Interrelated in Patients With Rheumatoid Arthritis

Abstract: The relationship among the gut microbiome, global fecal metabolites and rheumatoid arthritis (RA) has not been systematically evaluated. In this study, we performed 16S rDNA sequencing and liquid chromatography-tandem mass spectrometry (LC-MS/MS)-based nontargeted metabolomic profiling on feces of 26 untreated RA patients and 26 healthy controls. Twenty-six genera and forty-one MS2-identified metabolites were significantly altered in the RA patients. Klebsiella, Escherichia, Eisenbergiella and Flavobacterium w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 50 publications
(52 reference statements)
5
48
1
Order By: Relevance
“…However, Yang Sun et al found that the relative abundance of Bacteroides was increased in RA patients (35). Another study found that the relative abundance of Megammonas was increased in HCs (39), whereas our study found that the relative abundance of Megammonas was elevated in RA patients during the active and remission stage. Interestingly, we found that the relative abundance of Ruminococcaceae_Ruminococcus was also reduced in the active and remission stage of RA patients.…”
Section: Discussioncontrasting
confidence: 77%
“…However, Yang Sun et al found that the relative abundance of Bacteroides was increased in RA patients (35). Another study found that the relative abundance of Megammonas was increased in HCs (39), whereas our study found that the relative abundance of Megammonas was elevated in RA patients during the active and remission stage. Interestingly, we found that the relative abundance of Ruminococcaceae_Ruminococcus was also reduced in the active and remission stage of RA patients.…”
Section: Discussioncontrasting
confidence: 77%
“…Dysbiosis of specific bacterial lineages and alterations in gut microbiota metabolism led to changes in the host immune profile that contribute to RA ( 8 ). It has been proposed that the mechanism by which gut microbiota imbalance leads to RA may be related to regulation of immune function by metabolites produced by gut microbes ( 9 , 10 ). Immune T and B cells have position-specific phenotypes and functions in the mucosa, influenced by the microbiota ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…The study suggested that targeting the intestinal barrier is a potential strategy for treating autoimmune diseases such as RA (9). Some scholars have proposed that intestinal ecological disorders are related to the autoimmune mechanism involved in the development of RA (10). The gut microbiota produces metabolites that regulate host immunity and influence host resistance and susceptibility to disease.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have proposed that intestinal ecological disorders are related to the autoimmune mechanism involved in the development of RA ( 10 ). The gut microbiota produces metabolites that regulate host immunity and influence host resistance and susceptibility to disease.…”
Section: Introductionmentioning
confidence: 99%